2009
DOI: 10.1002/jid.1594
|View full text |Cite
|
Sign up to set email alerts
|

Mainstreaming the rights of persons with disabilities in national development frameworks

Abstract: Development practitioners and governments continue to grapple with how best to ensure the participation of socially excluded and marginalised groups in the development of poverty reduction strategy plans and national development programmes. This paper analyses the challenges involved in ensuring that persons with disabilities and their representative organisations are effectively included in such initiatives, using examples from recent practices in Uganda. It concludes by making some tentative recommendations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 3 publications
2
18
0
Order By: Relevance
“…A number of studies have reported that regular flow of social grants to beneficiaries is key to enable them to invest in productive income-generation activities (Banks et al, 2017; Gooding and Marriot, 2009; Mwendwa et al, 2009). This study, however, found that patterns in the release of funds were irregular as many of the participants had to wait for years before receiving the grant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have reported that regular flow of social grants to beneficiaries is key to enable them to invest in productive income-generation activities (Banks et al, 2017; Gooding and Marriot, 2009; Mwendwa et al, 2009). This study, however, found that patterns in the release of funds were irregular as many of the participants had to wait for years before receiving the grant.…”
Section: Discussionmentioning
confidence: 99%
“…Poverty is still prevalent among persons with disabilities in many low-income countries because of non-existent, or poorly implemented, social intervention programmes. Particularly, in countries where social programmes are available, studies have reported challenges encountered by persons with disabilities in their effort to have access (Banks et al, 2017; Devereux, 2010; Drucza, 2016; Goldblatt, 2009; Gooding and Marriot, 2009; Katsui and Kumpuvuori, 2008; Kuper et al, 2016; Loeb et al, 2008; Mitra, 2010; Mwendwa et al, 2009). For example, in Tanzania, Kuper et al (2016) found that persons with disabilities were not specifically targeted in existing social programmes and, as such, their needs were not taken care of.…”
Section: Social Protection and Persons With Disabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The approach advocated the inclusion of the voices of PWDs in all stages of disability development programming. However, according to recent reviews, there remains a long way to go before a disabilityinclusive approach is universally adopted in development (Kett et al, 2009;Mwendwa et al, 2009).…”
Section: Disability: Models Definitions Measures and Disability-incmentioning
confidence: 98%
“…In recognition of the fact that PWDs are disproportionately poor and socially excluded, there is a growing awareness among policy makers and development practitioners that PWDs must be included within poverty reduction strategy plans (Mwendwa et al, 2009). PWDs are increasingly being incorporated into national social protection programmes, which typically include cash transfer programmes, noncontributory health insurance programmes, community-based rehabilitation (CBR), vocational training and education programmes.…”
Section: Introductionmentioning
confidence: 99%